The gill transcriptome reveals unique antimicrobial features that protect Nibeaalbiflora from Cryptocaryonirritans infection. Issue 8 (29th April 2021) - Xie, Xiao; Jiang, Yunyan; Miao, Rujiang; Huang, Jiashuang; Zhou, Liyao; Kong, Jindong; Yin, Fei
Abstract: Cryptocaryonosis is the greatest threat to most teleost species among all parasitic diseases, causing mass loss to the marine aquaculture industry. Epidemiological investigation of teleost susceptibility to Cryptocaryon irritans infection revealed that yellow drum ( Nibea albiflora ) is highly resistant. In order to further understand the activation of the immune system in the gill, which is one of the main mucosal‐associated lymphoid tissues and a target of parasites, transcriptome analysis of the yellow drum gill was performed. Gill samples were collected from fish challenged after 24 hr and 72 hr with theronts at a median death rate (2050 theronts per gram fish). Gene expression profiles showed that TLR5 was the only receptor that activated the downstream immune response. The infection activated complement cascade through alternative pathway and increased the expression of C5a anaphylatoxin chemotactic receptor 1. In addition, possible antimicrobial molecules, including lipoprotein and haptoglobin, which are responsible for trypanolysis in humans, were among the top significantly upregulated genes at 24 hr. After 72 hr, the expression of secreted immunoglobulin T‐related genes was induced. These results suggested a rapid innate and adaptive immune response at the mucosal level. In conclusion, the results provide new perspectives on mucosal immune resistance in yellow drum against cryptocaryonosis and provide the possibility of mining resistance genes for future therapy.